Keabsahan Kontrak Kerja Konstruksi Yang Tidak Mencantumkan Klausul Pilihan Penyelesaian Sengketa Konstruksi - Zakaria, Iqbal; Danil, Elwi; Yuslim, Yuslim (Nagari Law Review, 2024)
The term "contract" in the construction services sector is known as a construction work contract. A construction work contract are included the category of innominate or unnamed contracts because it emerged and developed without specific regulation in the Indonesian Civil Code (Burgerlijk wetboek). Construction work contracts are specifically regulated under Law Number 2 of 2017 concerning Construction Services. According to Article 47, paragraph (1) of the Construction Services Law, one of the clauses that must be included in a construction work contract is the choice of dispute resolution for construction disputes. Furthermore, in the attachment to the Model Document Selection Regulation National Public Procurement Agency Number 12 of 2021, there are also provisions regarding the choice of dispute resolution clause in the general terms of contract and special terms of contract sections. The general terms of contract and special terms of contract are integral parts of a construction work contract, even though they are structurally separated into two different sections. However, in practice, there are still construction work contracts that do not include this clause. This study aims to analyze the validity of construction work contracts that do not include the choice of dispute resolution clause. The research method used is normative. The results of the study indicate that the presence of a construction dispute resolution choice clause is included as an element of naturalia. The naturalia element is an element in a contract/agreement that is still considered to exist and does not render the agreement invalid or non-binding on the parties who made it. If the choice of dispute resolution clause is not included in a construction work contract, it does not automatically render the contract invalid. The contract will remain valid as long as it meets the general requirements for the validity of a contract as stipulated in Article 1320 of the Indonesian Civil Code. However, it is important for parties involved in a construction work contract to include this clause because its presence can provide clarity and legal certainty in the execution of the construction work contract.